The Correlation between the Dermatology Life Quality Index and the Psoriasis Area Severity Index. Issue 1 (December 2015) - Leon, Argentina; Beroukhim, Kourosh; Danesh, Melissa; Nguyen, Catherine; Lee, Kristina; Farahnik, Benjamin; Hao Zhu, Tian; Abrouk, Michael; Wang, Eva; Malakouti, Mona; Brown, Gabrielle; Levin, Ethan; et al.
Background: Psoriasis patients experience a significant decrease in quality of life (QoL). Objectives: This study was conducted to prospectively measure changes in QoL of patients with moderate-to-severe psoriasis who are treated with ustekinumab. We performed a review of the literature, and discussed the significance of our results in the context of the controversy regarding the correlation between the Dermatology Life Quality Index (DLQI) and Psoriasis Area Severity Index (PASI). Methods: Seventeen patients with moderate-to-severe plaque psoriasis received 36 weeks of ustekinumab and were followed every 4 weeks. Results: All patients demonstrated significant improvement, both in terms of QoL and physical assessments. The data suggest a strong linear correlation between mean percent reduction in PASI and mean reduction in DLQI (R2=0.94). Conclusion: Psoriasis patients treated with ustekinumab achieved significant improvement of QoL, which correlated with physical improvement. This study demonstrates a strong correlation between mean percent reduction in PASI and mean reduction in DLQI.